Analisis Penggunaan Media Pembelajaran Audio-Visual Pada Mata Pelajaran Biologi Terhadap Hasil Belajar Siswa SMA Negeri 1 Nita: Analisis Penggunaan Media Pembelajaran Audio-Visual Pada Mata Pelajaran Biologi Terhadap Hasil Belajar Siswa SMA Negeri 1 Nita - Lengu, Maria Rusmiana (Jurnal Sains dan Pendidikan Biologi, 2022)
This study aims to determine the use of audio-visual learning media in biology subjects on the learning outcomes of students of SMA Negeri 1 Nita. This research was conducted at SMA Negeri 1 Nita in semester 2 of the school year 2021-2022. This study uses a qualitative descriptive approach method. In this researcher the data collection techniques used by interviews and documentation. With the respondents were biology teachers and 30 students in the class of MIA 1. The results were found that, the use of audio-visual media in biology subjects on class X student learning outcomes can help make it easier for student to understand the material and students ate motivated for learning enthusiasm so that it greatly affects learning outcomes that can be seen from student grades, the average 83 which is based on the interview value of 83-91, it can be categorized by a good value. Therefore, the results of this study concluded that the use of audio-visual media has a very good impact on student learning outcomes.